Development of Self-Management Skills as an Effort to Improve the Productivity of Teenagers in Babakan Banten Hamlet - Ummik, Mediatul; Endriyani, Yayuk; Azzahra, Virginia Fatima; Pangestuti, Rinda Siaga; Khatimah, Husnul (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aims to investigate productivity issues among productive-aged students in Babakan Banten within the context of Industry 4.0. It highlights the importance of self-management skills in meeting modern demands. Method: Utilizing a mixed-methods approach, combining surveys, interviews, and observations, this study examines the behaviors and self-management practices of students. Data were analyzed using statistical techniques to identify trends. Practical Applications: Findings inform tailored interventions for educators and policymakers to promote self-management skills. Community leaders can use insights to develop support systems for students, fostering holistic development. Conclusion: Self-management skills are crucial for addressing productivity challenges. This study provides insights for effective interventions, enabling students to thrive in the competitive landscape of Industry 4.0. Ongoing investment in such initiatives is essential for youth success.